Availability, Feasibility, and Implementation of Occupational Health and Safety Facilities in a Senior High School Chemistry Laboratory - Julyanis Fatko; Siti Aisyah Maulida; Siti Robi'atul Awaliyah; Putri Naila Lestari; Evi Muliyah (BIOCHEPHY: Journal of Science Education, 2026)
The school laboratory is an essential facility for conducting practical activities safely and effectively; therefore, adequate Occupational Health and Safety (OHS) facilities are required. This study analyzed the availability, feasibility, and implementation of OHS equipment and materials in the chemistry laboratory of SMA Negeri 6 Tangerang Selatan, Indonesia. A descriptive design integrating qualitative and quantitative approaches was employed. Data were collected through observations, interviews, and documentation using expert-validated observation checklists and interview guides. Quantitative data were analyzed using percentage calculations, while qualitative data were analyzed following the Miles and Huberman model. The findings revealed that the availability of OHS facilities reached 65.2% (complete category), while their feasibility reached 56.5% (adequate category). Existing facilities included personal protective equipment, fire extinguishers, first aid kits, fume hoods, sinks, and ventilation systems. However, eyewash stations, emergency showers, and clearly designated evacuation routes were unavailable, and some PPE was damaged. Overall, OHS implementation remains suboptimal and requires continuous improvement through regular maintenance, supervision, and facility provision.